Occurrence of OXA-48 Carbapenemase and Other β-Lactamase Genes in ESBL-Producing Multidrug Resistant Escherichia coli from Dogs and Cats in the United States, 2009–2013 - Liu, Xiaoqiang; Thungrat, Kamoltip; Boothe, Dawn M. (Frontiers in Microbiology, 2016)
The aim of this study was to explore the occurrence and molecular characterization of extended-spectrum β-lactamases (ESBL), plasmid-mediated AmpC β-lactamase (pAmpC) and carbapenemases among ESBL-producing multidrug resistant (MDR) Escherichia coli from dogs and cats in the United States. Methods: Of 2443 E. coli isolated from dogs and cats collected between August 2009 and January 2013, 68 isolates were confirmed as ESBL-producing MDR ones. PCR and sequencing were performed to identify β-lactamases and plasmid-mediated quinolone resistance (PMQR) genes, and shed light on the virulence gene profiles, phylogenetic groups and ST types. Results: Phylogenic group D and B2 accounted for 69.1% of the isolates. 50 (73.5%) isolates carried CTX-M ESBL gene, and the most predominant specific CTX-M subtype identified was blaCTX-M-15 (n=33), followed by blaCTX-M-1 (n = 32), blaCTX-M-123 (n = 27), blaCTX-M-9 (n=19) and blaCTX-M-14 (n=19), and blaCTX-M-123 was firstly reported in E. coli isolates in the United States alone or in association. Other β-lactamase genes blaTEM, blaSHV, blaOXA-48 and blaCMY-2 were detected in 41.2%, 29.4%, 19.1% and 17.6% of 68 ESBL-producing MDR isolates, respectively. The blaTEM and blaSHV genes were classfied as ESBLs with the exception of the blaTEM-1 gene. Additionally, 42.6% (29/68) of isolates co-expressed blaCTX-M-15 and PMQR gene aac(6')-Ib-c. The overall occurrence of virulence genes ranged from 11.8% (ireA) to 88.2% (malX), and most of virulence genes were less frequent among CTX-M-producing isolates than non-CTX-M isolates with the exception of malX and iutA. The 68 isolates analyzed were assigned to 31 STs with six being novel. Three pandemic clonal lineages ST131 (n=10), ST648 (n=9), and ST405 (n=9) accounted for more than 41% of the investigated isolates, and ST648 and ST405 of phylogenetic D were firstly reported in E. coli from dogs and cats in the United States. Conclusion: blaCTX-M-123 of ESBLs and carbapenemase blaOXA-48 were firstly reported in ESBL-producing MDR E. coli from dogs and cats in the United States, and ST131, ST648 and ST405 were the predominant clonal groups.